2004
DOI: 10.1007/s10682-004-5145-5
|View full text |Cite
|
Sign up to set email alerts
|

Clonal and genetic structure of two Mexican oaks: Quercus eduardii and Quercus potosina (Fagaceae)

Abstract: Quercus eduardii and Q. potosina are dominant oak species in Sierra Frı´a, Aguascalientes, Mexico. These species have been exploited for multiple purposes since the 16th century. Both species produce clonal offspring through root suckering and acorns through sexual reproduction. To understand clonality for the implementation of the most adequate actions for the conservation of these species, we addressed the following questions: (a) what is the spatial clonal structure of both species? (b) How much clonal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
3
14
0
6
Order By: Relevance
“…Although elasticity values show that clonal propagation is more important than sexual reproduction in terms of recruitment of these species, populations of Q. eduardii and Q. potosina also regenerate by means of sexual reproduction. A genetic study carried out with populations of Q. eduardii and Q. potosina in the same plots of this study in Sierra Fría, using random polymorphic amplified DNA (RAPDs) molecular marker, showed that almost 50% of the sampled individual plants of both species had a sexual origin (Alfonso-Corrado et al, 2004). These results suggest that seedling recruitment occurs sporadically in populations of both species, when a good crop is produced followed by specific environmental conditions such as winter rains.…”
Section: Discussionsupporting
confidence: 51%
“…Although elasticity values show that clonal propagation is more important than sexual reproduction in terms of recruitment of these species, populations of Q. eduardii and Q. potosina also regenerate by means of sexual reproduction. A genetic study carried out with populations of Q. eduardii and Q. potosina in the same plots of this study in Sierra Fría, using random polymorphic amplified DNA (RAPDs) molecular marker, showed that almost 50% of the sampled individual plants of both species had a sexual origin (Alfonso-Corrado et al, 2004). These results suggest that seedling recruitment occurs sporadically in populations of both species, when a good crop is produced followed by specific environmental conditions such as winter rains.…”
Section: Discussionsupporting
confidence: 51%
“…The clonal regenerative capability of Q. sideroxyla allows the undisturbed preservation of genotypes, a phenomenon that was also found in Q. eduardii and Q. potosina in the study zone [5] [8]. These typical life histories could be responsible for the preservation of the genetic diversity of a species, despite the prolonged years of intensive extraction and the changes in soil use that have occurred in the Sierra Fría during the 20th century [16] [17], and could have served as a damping capability against earlier disturbances at the local scale [8] [40].…”
Section: Genetic Diversitysupporting
confidence: 54%
“…The gravity seed dispersal system of Q. sideroxyla, common in Sierra Fría oaks [8] [9], could be responsible for the formation of family groups. Family groups in oaks generally occur at short distances (less than 20 meters) from the progenitor tree [39].…”
Section: Genetic Diversitymentioning
confidence: 99%
“…The value of AMOVA obtained for the genetic differentiation among populations in Q. suber in Portugal (Φst = 0.036) is within the range of values reported for those species (0.044 -0.030 for oaks over a large European range, 0.021 for Flemish oaks, 0.106 to 0.342 for California red oaks). KREMER and PETIT (1993) reported values from 0.02 to 0.17 for 33 oak species using allozymes markers, HAMRICK et al (1992) found a mean value of 0.11 for 28 oak species and ALFONSO-CORRADO et al (2004) values of 0.13 and 0.19 for two Mexican oaks, using RAPD's markers.…”
Section: Genetic Diversity Within and Among Populationsmentioning
confidence: 99%
“…Genetic diversity has also been assessed in Q. robur and Q. petrae using microsatellites and Amplified Fragment Length Polymorphism (AFLP) markers (COTTRELL et al, 2003;MARI-ETTE et al, 2002;COART et al, 2002), in California red oaks (DODD and KASHANI, 2003) using AFLP, and in Mexican oaks using RAPD's markers (ALFONSO-CORRADO et al, 2004). Conservation policies will depend to a large extent on our knowledge of historic and genetic relationship among these species.…”
Section: Introductionmentioning
confidence: 99%